(untitled) (Imagens da Educação, 2024)
This thematic call aims to bring together articles that reflect on issues related to teacher initiation during the covid-19 pandemic, in a movement of resistance and survival for the school, the teacher, and the future teacher, focusing on both the impossibilities and the possibilities realized in practice. In it, we present articles about the various programs and strategies used to adapt to the new impositions presented by the pandemic. The programs analyzed were PIBID, PRP, Teacher Residence, PID, and Teacher Initiation itself. We can conclude, from the articles presented, that the difficulties were many, but several possibilities emerged amidst reflections on initial and continuing teacher education, innovative and motivating pedagogical practices that benefited not only the students/teachers in initial education but also the teachers of basic schools and their respective students, in a partnership between university and school, in the relationship between teaching and learning, in a true theoretical-practical formation. Thus, we believe that this thematic call may contribute to reflections on the various forms of teacher education and pedagogical practices, not only in the context of the pandemic but also in the production of innovative strategies that can be developed in all educational contexts.